Effect of Nigella sativa seeds' extract Treatment on Neutrophils count - Al-Haidary, Batool A. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Nigella sativa seeds have been frequently used in folk medicine for treatment of various diseases such as inflammatory disease. The aim of thisstudy is to show the effect of this herb on Neutrophils count as the main antiinflammatory cells.Materials & Methods: Aqueous & oil extract ofNigella sativa seeds have been applied for treatment of 30 blood samples of apparently healthy individuals. Blood count has been performed after different incubation periods.Results & Conclusions: This study revealed that treatment of blood samples with herbal extraction results in highly significant elevation of Neutrophils'count with time passing particularly the aqueous one and after 6 hrs. incubation period (P < 0.001). Our conclusion, that Nigella sativa aqueousextract can be used against bacterial infections which required recruitment of Neutrophils.